Tranexamic acid: A strategy to decrease postoperative drainage in elbow arthrolysis while preserving joint function - Bao Zhao; Jinlei Dong; Guoming Zhang; Lianxin Li; Dongsheng Zhou; Shun Lu; Fanxiao Liu (Journal of Orthopaedic Surgery)
Background The study aims to evaluate the influence of tranexamic acid (TXA) on clinical outcomes in patients with elbow stiffness undergoing elbow arthrolysis. Methods A systematic review of records up to December 2024 was conducted to screen research examining the role of TXA in patients with elbow stiffness undergoing elbow arthrolysis. The primary outcomes of interest included blood transfusion, hematoma formation, operative time, postoperative pain measured by the Mayo Elbow Performance Score (MEPS), Visual Analog Scale (VAS), total blood loss, changes in hemoglobin, drain output, and complications. Results Following an extensive search of relevant databases, a total of seven studies involving 995 patients (491 in the TXA group and 504 in the non-TXA group) undergoing elbow arthrolysis were included. The pooled analysis showed that TXA administration was associated with a significant reduction in total drain output (MD = −55.34, 95% CI: −80.67 to −30.02, p = .0001) and blood loss (MD = −39.07, 95% CI: −69.71 to −8.43, p = .01) compared to non-TXA group. Furthermore, patients treated with TXA had higher postoperative hemoglobin levels (MD = 11.73, 95% CI: 8.74 to 14.73, p = .00001). No significant differences were observed in operative time, tourniquet time, or functional outcomes as measured by MEPS, VAS, or range of motion (ROM). The pooled results indicated that TXA was associated with a significant reduction in hematoma formation (RR = 0.43, 95% CI: 0.19 to 0.97, p = .04) compared to the non-TXA group. However, no significant differences were found in other complications. Conclusion The perioperative use of tranexamic acid is an effective strategy to reduce postoperative drainage in elbow arthrolysis while preserving joint function.